Casa Comercial Loreto Import S.A - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observo la Fachada de la casa comercial Loreto Import funcionando en las instalaciones de una Casona de la epoca del caucho , entre los jirones Prospero y Ricardo Palma.
ENGLISH: The facade of the commercial house Loreto Import was observed working in the facilities of a large house of the time of the rubber, between Prospero and Ricardo Palma shreds.

SPANISH: Se observo la Fachada de la casa comercial Loreto Import funcionando en las instalaciones de una Casona de la epoca del caucho , entre los jirones Prospero y Ricardo Palma.
ENGLISH: The facade of the commercial house Loreto Import was observed working in the facilities of a large house of the time of the rubber, between Prospero and Ricardo Palma shreds.
Commercial House Loreto Import S.A
Keywords: Iquitos (Perú)|~|Commerce and Groceries--Real Estate|~|Iquitos (Perú)|~|Bien Inmueble|~|Perú|~|Comercio y Abarrotes|~|Bien Inmueble|~|Iquitos (Perú)|~|Real Estate|~|Peru|~|Commerce and Groceries|~|Real Estate